2021
DOI: 10.1017/jsl.2021.85
|View full text |Cite
|
Sign up to set email alerts
|

Model Theory of Derivations of the Frobenius Map Revisited

Abstract: We prove some results about the model theory of fields with a derivation of the Frobenius map, especially that the model companion of this theory is axiomatizable by axioms used by Wood in the case of the theory $\operatorname {DCF}_p$ and that it eliminates quantifiers after adding the inverse of the Frobenius map to the language. This strengthens the results from [4]. As a by-product, we get a new geometric axiomatization of this model companion. Along the way we also prove a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Remark For scriptB=B$\mathcal {B}=B_\otimes$, adding just the inverse of the Frobenius map suffices to get quantifier elimination for scriptBprefixCF$\mathcal {B}-\operatorname{CF}$, which was proven in [1]. During the review process of this paper, the first author showed quantifier elimination results regarding the language with the inverse of the Frobenius map, which can be applied to the theories scriptBprefixCF$\mathcal {B}-\operatorname{CF}$ (see [7, Theorem 2.8])…”
Section: Model Theory Of B$\mathcal {B}$‐operatorsmentioning
confidence: 89%
“…Remark For scriptB=B$\mathcal {B}=B_\otimes$, adding just the inverse of the Frobenius map suffices to get quantifier elimination for scriptBprefixCF$\mathcal {B}-\operatorname{CF}$, which was proven in [1]. During the review process of this paper, the first author showed quantifier elimination results regarding the language with the inverse of the Frobenius map, which can be applied to the theories scriptBprefixCF$\mathcal {B}-\operatorname{CF}$ (see [7, Theorem 2.8])…”
Section: Model Theory Of B$\mathcal {B}$‐operatorsmentioning
confidence: 89%